1991
DOI: 10.1042/bj2730573
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of platelet-activating factor in human haematopoietic cell lines. Differences between myeloid and lymphoid cells

Abstract: The binding and metabolism of platelet-activating factor (PAF) was studied in human cell lines resembling myeloid cells (HL60 and U937) and B and T lymphocytes (Daudi and Jurkat). All of the cell lines were found to bind and catabolize exogenous [3H]PAF in a time- and temperature-dependent manner. PAF binding could also be demonstrated in isolated membrane fractions, which provides further evidence of the existence of true membrane receptors. Myeloid cell lines contained numbers of receptors at least 10-fold h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…In contrast, LysoPAFAT/LPCAT2 mRNA was undetected in T cells stimulation with or without anti-CD3 Ab for 24 h (data not shown). These results are in accord with previous reports demonstrating that LysoPAFAT activity is present in macrophages (4, 12), but not in T cells (42). The results are also consistent with our previous report that PAF plays a dominant role in the chronic phase of EAE through the activation of macrophages/microglia (16).…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, LysoPAFAT/LPCAT2 mRNA was undetected in T cells stimulation with or without anti-CD3 Ab for 24 h (data not shown). These results are in accord with previous reports demonstrating that LysoPAFAT activity is present in macrophages (4, 12), but not in T cells (42). The results are also consistent with our previous report that PAF plays a dominant role in the chronic phase of EAE through the activation of macrophages/microglia (16).…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, membrane PAF-Rs could be detected in a histiocytic lymphoma line and in peripheral blood neutrophils and monocytes from healthy donors [20]. Additionally, the findings of Garcia et al [21] showed the ability of myeloid cell lines (HL60 and U937) to synthesize PAF, in contrast to the absence of this property in the two lymphoid cell lines (Daudi and Jurkat). The clinical studies by Gugliemi et al highlight Brought to you by | MIT Libraries Authenticated Download Date | 5/11/18 6:53 PM membrane PAF-R in several types of chronic mature B-cell malignancies: chronic lymphocytic leukemia [22], mantel B-cell lymphoma, marginal zone B-cell lymphoma, plasma cell lymhoma, prolymphocytic or prolymphocytoid B-cell leukemia, and follicular B-cell lymphoma [23].…”
Section: Resultsmentioning
confidence: 71%
“…However, with regard to apoptosis, PAF was not able to induce DNA degradation in U937 cells and WEB‐2170 did not prevent the ET‐18‐OCH 3 ‐induced apoptosis (Figure 1a). It is interesting to note that PAF is converted to 1‐alkyl‐2‐acyl‐glycero‐3‐phosphocholine at a rate of about 50% per hour (García et al , 1991). However, even at this high rate of conversion the concentration of unmodified PAF would still be above 10 −9 m after 12 h, which is able to produce over 80% of the maximum effect on [Ca 2+ ] i (see below, Figure 4).…”
Section: Resultsmentioning
confidence: 99%